Output Feedback Variable Structure Control Design for Uncertain Nonlinear Lipschitz Systems - Jeang-Lin Chang; Tsui-Chou Wu (Journal of Control Science and Engineering)
This paper develops a full-order compensator-based output feedback variable structure control law for uncertain nonlinear Lipschitz systems having matched perturbations. Given that the sufficient condition is satisfied, the developed control scheme, with the observer-like technique incorporated into the design of the compensator, can achieve global exponential stabilization. An illustrative example is provided with simulation results to show the effectiveness of the proposed method.